Investigated optical and elastic properties of Porous silicon: Theoretical study - Yarub, Al - Douri; Nasser Mahmoud, Ahmed; N., Bouarissa; A., Bouhemadou (Elsevier Ltd., 2011)
Link to publisher's homepage at www.elsevier.com